(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Health is closely related to the economic development of the country, the conditions and standard of living, education, culture, as well as the way of life of the population. Much depends on the socio-economic situation, dietary restrictions, high psycho-emotional tension, can lead to a decrease in the standard of living. This is manifested primarily in the state of health of medical personnel. Our research allowed us to study the incidence, lifestyle and working conditions of medical workers from a socio-hygienic point of view.